Economic and Financial Challenges for Eastern Europe : Proceedings of the 9th International Conference on the Economies of the Balkan and Eastern European Countries in the Changing World (EBEEC) in Athens, Greece, 2017 /: Proceedings of the 9th International Conference on the Economies of the Balkan and Eastern European Countries in the Changing World (EBEEC) in Athens, Greece, 2017. ([2019]) - Unknown
No abstract available